Mechanisms of global climate change during the five major mass extinctions - Kunio Kaiho (Scientific Reports)
Abstract Since the emergence of diverse animal phyla around 500 million years ago, five major mass extinction events have occurred, each coinciding with abnormal climate changes. We analyzed sedimentary organic molecules from the first and least understood extinction event at the end of the Ordovician period. We divided all five major extinctions into two phases each, totaling ten events, and examined the relationship between climate shifts and the “coronene index”—an indicator of heating temperatures in sedimentary rocks caused by volcanic activity or meteorite impacts. As a result, we found that four of the five extinctions began with global cooling and ended with warming, while one started with an unknown anomaly and also ended with warming. During the initial extinction phases, two events showed low-temperature heating, two high-temperature, and one moderate-temperature. All subsequent warming phases showed moderate-temperature heating. These findings suggest that large-scale volcanic eruptions and meteorite impacts heated sulfides, sulfates, and hydrocarbons at varying temperatures, releasing SO2 or soot into the stratosphere, blocking sunlight, and triggering global cooling and extinction. This was followed by moderate heating of hydrocarbons and carbonates, increasing CO2 emissions and driving long-term global warming, leading to secondary extinction events.